A multivariate dataset on profiling personality traits, social and cognitive determinants of omani students’ entrepreneurial intention - Imran Saleem; Imran Anwar (Data in Brief, 2023)
This data article collects and validates a multivariate dataset on personality traits, social, and cognitive predictors of the entrepreneurial intention of 276 students of three Omani universities. Administering a validated questionnaire, a pilot study was conducted by taking a sample of 60 responses to ensure the robustness of the survey scales. Following the pilot study, the final data were collected from 276 UG and PG level students in February 2021, which were first cleaned for missing, unengaged, and outlier responses before going ahead with statistical analyses. The data were also checked for common method bias by applying Cook's distance method which was followed by establishing the measurement model (ensuring model fitness, convergent and divergent validities) by running a CFA model in AMOS. The dataset from this data article would be of significant use for the researchers studying nascent and student entrepreneurship and Oman universities and the government in developing an entrepreneurship course curriculum.